Rethinking the Teaching of Art Direction: Teaching Strategies and their impact on the development of competencies in Audiovisual Communication Students at a private University in Metropolitan Lima - Aguilar Florindo, Ximena (2025)
The Art Direction course in the Audiovisual Communication program requires teaching strategies that go beyond theoretical exposition and foster the development of professional competencies related to aesthetic production, visual creativity, and collaborative work. The present article is framed within a qualitative, hermeneutic approach, aimed at critically understanding the teaching strategies used in the Art Direction course at a private university in Metropolitan Lima, and their relationship with the development of professional competencies in students of Audiovisual Communication. Through documentary analysis, a review of specialized literature, and a contextual interpretation of the course syllabus, the study seeks to reflect on the limitations of the traditional approach and to propose pedagogical alternatives based on active, collaborative, and applied methodologies. Although the broader research project involves a quasi-experimental design with the collection of quantitative data through pre- and post-intervention tests, this article represents a preliminary theoretical and reflective stage that supports and justifies the need to rethink teaching practices in line with a competency-based approach. Preliminary findings indicate significant improvements in the experimental group in competencies such as visual planning, teamwork, discourse analysis, aesthetic decision-making, and creative problem-solving. The comparative analysis shows greater progress in the intervened group, both in test results and practical evaluations. It is concluded that the use of project-based strategies, active and applied methodologies, role-playing simulations, and experiential learning contributes to the development of key competencies in the Art Direction course and enhances academic performance, student motivation, and professional preparation in the field of Audiovisual Communication.